Unveiling Speech Styles : A Sociolinguistics Analysis of Steve Harvey’s Talk Show - Prastowo, FR Suluh Adiguna; Fiani, Ani; Syafitri, Dewi (JELLT (Journal of English Language and Language Teaching), 2024)
This research analyzed the types of speech style used by Steve Harvey in his talk show videos. The objectives of this research were to describe types of speech style based on Joos’s theory occurred in Steve Harvey’s talk show videos. The method of the research was a descriptive qualitative. The technique for collecting the data was audio-visuals. The researcher used videos talk show of Steve Harvey uploaded in January 2024 on Steve TV Show YouTube channel. There were 9 talk show videos uploaded on January 2024. In this research, the researcher found some types of speech style contained in talk show videos consist of 177 (90,77%) casual styles, 9 (4,62%) intimate styles, 5 (2,56%) formal styles, and 4 (2,05%) consultative styles. In conclusion casual style 177 (90,77%) is the most dominant used by Steve Harvey in his talk show videos in January 2024. Keywords: Sociolinguistics, Speech Styles, Talk Show